Complete Poems - McKay, Claude, 1890-1948 (Book collections on Project MUSE., 2008)
"Containing more than three hundred poems, including nearly a hundred published here for the first time, this collection showcases the range of Claude McKay (1889-1948), the Jamaican-born poet and novelist whose life and work were marked by restless travel and steadfast social protest."--Jacket